Salivary Vascular Endothelial Growth Factor and Epidermal Growth Factor Levels in Patients with Recurrent Aphthous Stomatitis: a Meta-Analysis - Paria Motahari; Davood Fathollahzadeh; Amir Alipour (Shiraz University of Medical Sciences, 2023)
Recurrent aphthous stomatitis (RAS) has been identified as a common oral lesion with an unknown pathogenesis. Various studies have been conducted to show the important role of two factors named epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF) in RAS, but certain results have not been achieved. The present meta-analysis was conducted to evaluate the salivary levels of EGF and VEGF in patients with RAS. For this purpose, the related articles in the Web of Science, PubMed, Embase, ProQuest and Scopus databases until January 2022 were searched and their abstracts were studied. Google scholar and scientific information database were also searched for articles in Persian. The searches were completed by the medical subject heading terms considering "recurrent aphthous stomatitis" and "saliva" in combination with "EGF" or "VEGF" keywords. All case control studies that evaluated the salivary levels of EGF and VEGF in patients with RAS were included in this study. To evaluate statistical heterogeneity between the studies, Cochrane Q and I2 tests were adopted. The extracted data then were used in the analysis process based on comprehensive meta-analysis software. Originally, 619 articles were considered, of which 7 articles were selected. According to this meta-analysis, salivary EGF and VEGF levels were significantly lower in the active and remission period of RAS than in healthy individuals (p Value< 0.05). In addition, salivary levels of these factors were significantly lower in the active stage of RAS than in the healing phase. This review study suggests that decreasing of salivary EGF and VEGF levels have significant role in the development of RAS.